THE EFFECTIVENESS OF TEACHING READING USING JIGSAW (AN EXPERIMENTAL RESEARCH AT FIRST YEAR STUDENTS OF SMP MUHAMMADIYAH 1 KARTASURA) - HARJANTI, SALIS (2010)
This research aims at knowing the effectiveness of teaching reading using jigsaw to the first year students of SMP Muhammadiyah 1 Kartasura. To collect the data, the writer used a test. The type of test is multiple choice. Here, the writer gets the numerical data and to analyze the data, the writer uses T-test. T-test is a technique for analyzing data that is used to compare the mean score between two groups of students. The writer compares the mean score of control group and experiment group, and she gets tarithematic > t-table (1, 97 >1, 66). Consulting to the result of computation in tarithmetic, the writer concludes that there is a difference in achieving reading mastery. It means that students who are taught using jigsaw have higher score than students who are taught using traditional method. In general, the writer concludes that teaching reading using jigsaw can encourage the students' ability in mastering reading. By using jigsaw, the students have cooperative team work. During the activities the students were helped to do the reading material by discussing as a team.